Analysis of intrinsic elements of poetry for class IV students of SDIT Insan Karima Cigombong - Salsabila Qurotu'ain (Mitra Palupi, 2023)
Background: Poetry is results work literature, which arises from expression feelings and thought, and arises in situation certain. Thing this seen in statement that nothing, rhythm, and pressure play role important in poetry, language imaginative and choice say (vocabulary) arranged by bait, which is total CLASSIFIED in each table, and so on. Poetry is of course not a simple work of art, but a very complex organism. Poetry is created with different linguistic and aesthetic elements. Poetry is also an important record and interpretation of human experience and is written in the most memorable form. There are two main elements in building a poem, namely intrinsic and extrinsic elements. Purpose: The purpose of this study was to determine students' ability to compose poetry based on the intrinsic elements of class VI SDIT Insan Karima. Design and methods: The research was conducted using a qualitative approach. The method used by researchers is descriptive qualitative. The subjects in this study were documents made by students, totaling 17 poems. The data collection tool used by the researcher was a document written by a class IV student at SDIT Insan Karima and filling in the rubric carried out by the researcher was based on the theory of Saefu Zaman Results: The results of this study are that out of 17 student works, almost 100% of the poems made are in accordance with the intrinsic elements requested, but the need for further guidance to students in managing vocabulary that will be poured into these poems.